Cardiovascular mortality and morbidity following radical radiotherapy for lung cancer: Is cardiovascular death under-reported?. (August 2020) - Sun, F.; Franks, K.; Murray, L.; Lilley, J.; Wheller, B.; Banfill, K.; McWilliam, A.; Abravan, A; Van Herk, M.; Faivre-Finn, C.; Cubbon, R.
Highlights: Cardiac toxicity from lung cancer radiotherapy is a recognised side effect. Cardiac death is under-reported in patients who received lung cancer radiotherapy. This adds to the difficulty of investigating radiotherapy related cardiac damage. Abstract: Background: Lung cancer is the most common malignancy worldwide. Radical radiotherapy is an essential treatment in the management of early and locally advanced lung cancer. Cardiac events are known to occur following radical radiotherapy for lung cancer. This study examines the burden of cardiac events post radiotherapy, and estimates the accuracy of death certification in patients who received radical radiotherapy for lung cancer. Methods: We conducted a retrospective observational cohort study for all patients receiving radical radiotherapy for non-small cell lung cancer (NSCLC) at a large cancer centre between 01/01/2010 to 31/12/2016. Baseline cardiovascular disease and cancer status and treatment data were collected, along with hospital admission data and documented cause of death from the national registry for a median follow-up period of 34 months. Results: Of 1224 patients included in the analysis, 378 (30.9%) patients had cardiovascular disease at baseline, including 140 (11.4%) with prior myocardial infarction. In the 846 patients without known cardiovascular disease, 451 (53.3%) had a QRISK2 predicted 10-year cardiovascular risk >20% over 10 years. During follow-up, 215 hospitalisations occurred (Incidence rate 6.2 per hundred patient years) which were classified as primarily cardiac, and 622 patients died (18 per 100 patient-years). However, death certificates stated a primary cardiac cause of death in only 33 cases (5.3% of deaths). Notably, 29% of patients dying out of hospital and certified as cancer death did not have documented cancer relapse prior to death, and 61% had no community palliative care input prior to death, implying these events may have been sudden and unexpected. Conclusion: There is a high prevalence of baseline cardiovascular disease in people undergoing radiotherapy for NSCLC, accompanied by significant rates of post-radiotherapy cardiovascular hospitalisation. However, only a small proportion of deaths are attributed to cardiovascular disease, together with the large amount of sudden deaths observed, this suggests that cardiovascular death is greatly under-reported in official statistics.